Patient and system delays in the treatment of acute coronary syndrome - Viana, M (2020)
Introduction Early reperfusion for patients with ST-segment elevation myocardial infarction (STEMI) is indicated by the European Society of Cardiology, while a timely invasive strategy is recommended for patients with high-risk and intermediate-risk non-ST-elevation acute coronary syndromes (NSTE-ACS). This study aims to assess patient and system delays according to diagnosis and risk profile, and to identify predictors of prolonged delay. Methods We assembled a cohort of patients (n=939) consecutively admitted to the cardiology department of two hospitals, one in the metropolitan area of Porto and one in the north-east region of Portugal, between August 2013 and December 2014. Results The proportion of patients with time from symptom onset to first medical contact (FMC) ≥120 min was highest among high-risk NSTE-ACS (57.7%), followed by intermediate-risk NSTE-ACS (52.1%) and STEMI (43.3%). Regardless of diagnosis and risk stratification, use of own transportation and inability to interpret cardiac symptoms correctly were associated with prolonged delays. Regarding system delays, we found that 78.0% of patients with STEMI and 65.8% of patients with high-risk NSTE-ACS were treated in a timeframe exceeding the recommended limits. Admission to a non-percutaneous coronary intervention-capable hospital, admission on weekends and complications at admission were associated with prolonged delays to treatment. Conclusions Due to both patient and system delays, a large proportion of STEMI and high-risk NSTE-ACS patients still fail to have access to timely reperfusion.